2017
DOI: 10.1371/journal.pone.0175138
|View full text |Cite
|
Sign up to set email alerts
|

Are fundamental niches larger than the realized? Testing a 50-year-old prediction by Hutchinson

Abstract: For more than 50 years ecological niches have been defined as combinations of multidimensional environmental conditions permitting a species to survive and reproduce. A fundamental niche (NF) is defined as the set of conditions within which a species can live in the absence of competitors, and a realized niche (NR) is a NF hypothetically reduced by competitive interactions (and some other limiting factors). This definition implies that NF is “larger” than NR, something that has been nearly universally accepted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
120
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(141 citation statements)
references
References 52 publications
4
120
0
4
Order By: Relevance
“…This is smaller than the fundamental niche, which is related to species physiological limits [39]. Booth et al [5,40] believe that under climate change long-lived trees, already well-established at a particular site, may be able to show some of the climatic adaptability that they show in trials outside of their natural distributions.…”
Section: Simulation Uncertainty and Its Applicationmentioning
confidence: 99%
“…This is smaller than the fundamental niche, which is related to species physiological limits [39]. Booth et al [5,40] believe that under climate change long-lived trees, already well-established at a particular site, may be able to show some of the climatic adaptability that they show in trials outside of their natural distributions.…”
Section: Simulation Uncertainty and Its Applicationmentioning
confidence: 99%
“…The potential impacts of short‐term human‐induced climate change on biodiversity have been extensively evaluated (Parmesan and Yohe , Parmesan , Bellard et al , Garcia et al , Pecl et al ). This research program found widespread evidence that phenology and demography of species are correlated with different dimensions of climate, with varying strength across geographical and environmental gradients.…”
Section: Introductionmentioning
confidence: 99%
“…This research program found widespread evidence that phenology and demography of species are correlated with different dimensions of climate, with varying strength across geographical and environmental gradients. Thus, under climate change, projected responses potentially include shifts, contractions and even collapses of species’ geographic ranges, with consequences for emergent broad‐scale biogeographic patterns, such as species richness gradients, community turnover and patterns of phylogenetic and functional diversity (Thuiller , Diniz‐Filho et al , Thuiller et al , Loyola et al , Sales et al ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations